Reconstructing Islamic Religious Education Test Instruments Through Authentic Digital Assessment - Reza Setya Rachman; Dina Hermina; Sheila Rosalia (Classroom: Journal of Islamic Education, 2026)
The advent of digital transformation and the emergence of generative artificial intelligence appear to have challenged conventional assessment practices within Islamic Religious Education, particularly concerning the treatment of written examinations as the primary evidential measure of students' religious comprehension. This article seeks to effect a reconstruction of assessment instruments in Islamic Religious Education through the integration of written, oral, and performance evaluations within an authentic assessment framework. This study utilizes a descriptive-analytical approach, grounded in a comprehensive examination of extant literature pertaining to educational evaluation, authentic assessment, Islamic Religious Education assessment, digital learning, and artificial intelligence in education. The findings suggest that while written tests may retain utility for assessing conceptual understanding, religious reasoning, and textual literacy, they appear insufficient for encompassing oral competence, worship practices, moral conduct, and the internalization of Islamic values. Oral tests are needed to verify the depth and authenticity of students' understanding, while performance tests are essential for assessing worship skills, religious behavior, and value-based action. This article proposes the development of an integrative assessment model, which is predicated upon the triangulation of written, oral, and performative evidence, substantially supported by digital technology. The model positions technology as a tool for documentation, feedback, and portfolio management, while teachers remain the central pedagogical interpreters of students' religious learning evidence.